The way of all fish [large type] - Grimes, Martha (Thorndike Press large print core series., 2014)
Hitmen Candy and Karl once again venture into the murky Manhattan publishing scene. This time they come to the aid of a writer who is being sued by her unscrupulous literary agent, L. Bass Hess, a man determined to get a 15 percent commission for a book he didn't sell. The unusually ethical contract killers join forces with publishing mogul Bobby Mackenzie and megabestselling writer Paul Giverney to rid the mean streets of Hess, not by shooting him, but by driving him crazy. They are helped by other characters from Foul Matter and a crew of new colorful personalities, including an out-of-work Vegas magician, an alligator wrangler, a glamorous Malaysian con lady, and Hess's aunt in Everglades City, who has undergone a wildly successful sex change.